1991
DOI: 10.1007/bf01244703
|View full text |Cite
|
Sign up to set email alerts
|

BMY 21502 and piracetam facilitate performance of two-choice win-stay water-escape in normal rats

Abstract: Sprague-Dawley rats given either 5 or 10 mg/kg of a new compound, BMY 21502, 150 mg/kg of piracetam or a dose of methylcellulose vehicle (p.o.) daily for 38 days beginning two days before training were compared on performance of a win-stay water-escape task in a circular water maze requiring the use of working memory. The task involved giving the rats pairs of trials in which the location of a submerged escape platform remained the same within a pair of trials but changed semirandomly across pairs. Rats receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…One is the visible discrimination learning task [7][8][9]34] and the other is the T-maze-type place discrimination task [16][17][18][19][20]. The allocentric place discrimination task, however, differs from above two tasks in some important points.…”
Section: Discussionmentioning
confidence: 99%
“…One is the visible discrimination learning task [7][8][9]34] and the other is the T-maze-type place discrimination task [16][17][18][19][20]. The allocentric place discrimination task, however, differs from above two tasks in some important points.…”
Section: Discussionmentioning
confidence: 99%
“…The well-known memory-enhancing capacity of piracetam has been studied in a large number of studies in rodents and humans [13]. There is evidence that piracetam not only enhances long-term memory but also affects immediate working shortterm memory [4,16]. Furthermore, animal experiments [5,24] as well as clinical studies in humans [2,6,23] have shown that piracetam also provides neuroprotective effects.…”
Section: Introductionmentioning
confidence: 99%
“…When preliminary research revealed that mice are incapable of performing a single-test-run version of a water-escape working memory task that we have used many times to test rats (Comer & Means, 1989; Means, Comer, & Moore, 1991; Means & Dent, 1991; Means & Kennard, 1991), we conducted an experiment examining variations of the task that provided the mice with more exposures to the trial-dependent information. Thus, Experiment 1 compared three versions of a working memory water-escape task, and Experiment 2 tested the effects of repeated glucose injections on performance of the version of the task found to be optimal for testing mice.…”
mentioning
confidence: 99%